A possibility to synchronously improve the high-temperature strength and ductility in face-centered cubic metals through grain boundary engineering. (October 2020) - Guan, X.J.; Shi, F.; Ji, H.M.; Li, X.W.
Abstract: To examine the influence of grain boundary engineering (GBE) on the high-temperature mechanical properties of face-centered cubic (FCC) metals, the tensile tests were carried out at 723 K on the non-GBE and GBE Cu-16at.%Al alloy samples. The GBE treatment increases the deformation uniformity and cracking resistance, thus effectively improves the high-temperature ductility. Moreover, the dynamic recrystallization (DRX) of the GBE sample is significantly suppressed due to the reduction of the Gibbs free energy, impeding the high-temperature softening. Therefore, the high-temperature strength and ductility of FCC metals might be synchronously improved by a GBE treatment under the premise that DRX occurs. Graphical abstract: Image, graphical abstract